Solid bulk shipping: cargo shift, liquefaction and the transportable moisture limit - Rose, T (2014)
If some solid bulk cargoes such as concentrates, unprocessed nickel ores and iron ore fines contain sufficient moisture, then cargo compaction during a voyage may cause liquefaction. This has been known to result in major cargo displacement ('cargo shift'), causing the vessel to capsize. This has resulted in a number of fatalities. To provide context to this interdisciplinary problem, an overview of the key considerations is presented, which includes: (i) a summary of the wide range of factors that influence a cargo's likelihood to shift; (ii) the soil mechanics principles that can be used to explain cargo shift; and (iii) the regulatory controls that are used to prevent its occurrence during shipment. Under the requirements of international maritime regulation, primarily the International Maritime Bulk Solid Cargoes (IMSBC) Code, a cargo that may liquefy must be shipped below a threshold moisture content, the 'Transportable Moisture Limit' (TML)—as determined from one of three laboratory test methods specified within the IMSBC Code. However, there are recognised problems with these tests, namely that for any given sample tested: (i) the tests give variable TML results, particularly when conducted in different laboratories; and (ii) each of the three test methods give a different TML result. As the TML determines a cargo's transportability, these issues have commercial and safety implications. To address these issues for the two most popular test methods, the Flow Table Test (FTT) and Proctor/Fagerberg Test (PFT), tests were performed on sand and iron ore fines. For each test, major sources of variability were identified, along with issues inherent in the test methodology. From these findings, a number of recommendations and several modifications have been proposed that, if implemented within the IMSBC Code, will improve the tests' reliability. The results were then compared to establish whether the different TML results obtained from the two test methods could be aligned—this showed that calibration between the methods was not possible on the basis of their TML. The test method assessment also incorporated observations at TML test facilities, interviews with leading researchers and an assessment of archive research material. Whilst the findings related to variability will help improve the reliability of the TML test methods, the accuracy of these methods is still not understood (i.e. how well do they indicate the likelihood for an actual cargo to liquefy?). This thesis therefore gives consideration to the likely accuracy of the TML test methods. It presents an improved representation of the cargo shift problem, with a view of providing future researchers with a basis to further assess this accuracy and thus the suitability of the TML as a criteria to detect cargoes which may liquefy.